“Long hard-ſounding Latin name[s]”: Applying Historical Ethnobotany to the Loddiges Plant Nursery (1818–1830) - Maki, Ethyn (Ethnobiology Letters, 2024)
Despite their potential, nursery stock catalogs have been overlooked in previous ethnobotanical studies. Here, this gap is addressed by surveying nursery-based plant knowledge cultivated within the historic British Loddiges nursery through an analysis of their stock catalogs dating from 1818 to 1830. Employing a historical ethnobotanical approach, the topics of categorization, nomenclature, and sourcing practices in the Loddiges nursery are examined while also exploring the methodological considerations of utilizing nursery stock catalogs in ethnobotanical research. Findings underscore the pragmatic nature of nursery-based plant knowledge, offering insight into the relationship between nurserymen and the plants they cultivated. This essay aims to clarify how sources such as stock catalogs can enrich historical ethnobotanical investigation and broaden the scope of ethnobotanical research to include topics such as commercial plant nurseries.